Problems in Development of Gannan Navel Orange and Recommendations - Chen, Yayan (Asian agricultural research, 2017)
The rapid development of Gannan navel orange industry has made it become a regional superior industry in China. However,with the rapid expansion of the planting scale,the market dilemma of ' vast planting but low income' of navel orange growers is increasingly deteriorating,and Gannan navel orange industrial system is to be further transformed and upgraded. Taking the quality and marketing as the bottleneck of industrial development,this paper analyzed factors influencing these two aspects. It came up with recommendations,including building superior regions,improving industrial quality and safety,and stressing multi-dimensional marketing,relying on government,enterprises,scientific research institutions,colleges and universities,non-governmental organizations,and navel orange growers,to promote high efficient and sustainable development of Gannan navel orange industry.